Liability of The Land Deed Making Officer (P PAT) as a General Officer for The Cancellation of The Sale and Purchase Deed Due to Unlawful Acts - Christy Monaita Martanti; Yoni Agus Setyono (IHSA Institute, 2022)
The Land Deed Maker Official (PPAT) is a public official who is authorized to make authentic deeds regarding certain legal actions in terms of the transfer of land rights, one of which is the deed of sale and purchase. In relation to its authority, PPAT is required to be responsible for the deed made and must uphold the dignity of the profession. In carrying out his profession, there are still violations committed by PPAT such as making a sale and purchase deed that is illegal (onrechtmatige daad), which results in the deed being null and void by a court decision. The research method used is normative legal research. The results of this research discussion are PPAT's responsibility for unlawful acts in carrying out their profession, namely the imposition of administrative sanctions. As for the deed which is declared null and void by a court decision, it is deemed to have never existed. That is, from the beginning the law considered that there had never been a sale and purchase.